The Effect of Working From Home on The Productivity of Female Lecturers During Covid-19 Pandemic At Private Universities In Indonesia - Gultom, Elida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
The research aims to knowing how the effect of work from home (WFH) on the performance of female lecturers during the Covid-19 pandemic at private universities in Pekanbaru City, Indonesia. The sample in this study were all female lecturers at the Higher School of Economics in Pekanbaru City, totaling 53 respondents, the sample technique used was accidental sampling technique. The data analysis technique used was Simple Linear Regression with the help of SPSS version 23 program. The results of this study are based on the results of a partial test (T test) obtained that work from home has a significant effect on the productivity of female lecturers at private universities in the city of Pekanbaru. The magnitude of the effect of work from home on the productivity of female lecturers is 26.9% while the remaining 63.1% is influenced by other variables outside of the study.